Alcohol consumption and atrial fibrillation risk: An updated dose-response meta-analysis of over 10 million participants - Jiang, Hezi; Mei, Xiaofei; Jiang, Yufeng; Yao, Jialu; Shen, Jinsheng; Chen, Tan; Zhou, Yafeng (Frontiers in Cardiovascular Medicine, 2022)
We conducted a dose-response meta-analysis on the relationship between alcohol consumption and risk of atrial fibrillation. We merged the data of over 10 million participants and found gender differences in the pattern of response to alcohol consumption. The relationship between AF risk and alcohol consumption is linear in men, while a potential non-linear J-shaped relationship is shown in women. In summary, this research is vital in furthering our understanding of the role of alcohol consumption in new-onset AF, especially among different genders.